Developing of Android Application "Ku Pantomime" for Junior High School Students - Welly Suryandoko; Heru Setyono; Rudloffudin Jindan (AL-ISHLAH: Jurnal Pendidikan, 2023)
The main purpose of this study is the development of the Android application "Ku Pantomime" to strengthen knowledge and pantomime skills in junior high school students. Android application "Ku Pantomime" is an interactive learning feature for Mime's knowledge and skills. Development research with the Addie model approach consists of five stages of implementation. The research implementation stage reaches the product development stage. This research instrument is a guideline for interviews, expert validation instruments, questionnaires, and observation sheets. Data were analysed using the mixed method. This research successfully developed an interactive, effective, and practical "Ku Pantomime" Android application. The results of this study are the answers to the problem of scarcity of learning media pantomime and teacher competencies in the field of Pantomime. As well as answering online learning design challenges by providing online learning media innovations at home.